PENERAPAN STRATEGI START UP PADA BISNIS YANG BERFOKUS PADA PRODUK MAKANAN - Fitra Jaya (Mount Hope Economic Global Journal, 2023)
Tawangmangu is one of the sub-districts in Karanganyar Regency with the majority of jobs as farmers. One of them is bananas which are widely available in the area, bananas can be processed into various various processed foods. Therefore, this research is to prove that product innovation can affect sales volume in business, currently the culinary business is growing rapidly in Indonesia. Start Up is a new business that is still in the development stage. Banana Chips is a snack product made from bananas which is innovated with various flavors ranging from savory, sweet and spicy. The use of bananas is not only for making banana chips but for various other processed food innovations such as melted banana chips and flour from banana peels which are no longer used or wasted. This innovation can add added value based on the benefits of wasted products. Marketing strategies used with digital marketing include Instagram, WhatsApp and Facebook.